Robotic System For Hazardous Chemical Experiment - Jenny, Teh Cheng Choo (2002)
Normally the experiments conducted in laboratories are done manually. This may lead to unpredictable accidents. It can cause damage to both experiment apparatus and its user. Results obtained from the experiment conducted manually are not accurate especially if the same experiment has to be repeated for many times. This technique needs to be improved. The main objective of this project is to provide a robotic system that is capable of handling hazardous chemical processing and experiments at laboratories. It can be reprogrammed to perform various tasks with flexible degrees of freedom. This system is called Robolab. This project starts from the development of a simple concept of XYZ movements and gripper, into a final form of a Cartesian robot. The main structure of the Robolab can be divided into software and hardware parts. The software is responsible to drive the robotic arms in order to move to a precise position and at the same time control the inputs and outputs devices of the system. The program consists of various functions such as home routine, stop routine, process routine, jog/manual routine and on-error routine. Meanwhile, the hardware of the Robolab system can be divided into electrical and mechanical modules. The electrical module consists of a power distribution system, a SmartStep/3 control board and a personal computer. The mechanical consists of an end effector, a pneumatic system, a Z-axis module, a Y-axis module, an X-axis module, a pipette module, a vibrator module, a conveyor belt system, a system base and jigs and fixtures module. A personal computer is needed to download program into the EPROM of the motion controller through the connection of RS232 host link system. The motion controller acts as the main processor of the robotic system. The actuators are used to drive the mechanical robotic arm. This robot also has a built-in fault detection system. It will inform its main controller if any particular faults occur to the system.The SmartStep/3 controller is chosen for this project to control the robot. CTERM, a terminal emulator is specially configured for the controller to use on pc. MlNT's flexible and powerful command set is used as a solution to motion control applications. From the experimental results, it is proven that the proposed robotic arm was successfully designed, constructed and controlled.